Synchronous removal and separation of multiple contaminants by poly (vinylidene fluoride)/polyaniline ultrafiltration membrane. Issue 6 (December 2022) - Ding, Jie; Zhang, Wenkai; Dai, Xin; Yao, Jiaming; Gao, Guandao
Abstract: Organic-inorganic complex pollution was widely coexisting in natural water bodies, poses serious environmental threats and is difficult disposed due to its complexity containing high organic matter, heavy metals and inorganic salts. Herein, we reported multi-functional polyvinylidene fluoride (PVDF)/polyaniline (PANI) ultrafiltration membranes, via the phase inversion process, for simultaneous separate and remove specific pollutants based on the sieving and adsorption mechanism. Compared with the pure PVDF membrane, the permeability of composite membrane was significantly improved nearly 6.2-fold from 31.3 ± 5.4 to 193.5 ± 13.7 m −2 h −1, benefiting from improved membrane hydrophilicity and porosity by PANI introduction, while higher rejection (from 67.4 % to 91.3 %) and excellent anti-fouling performance for the BSA were achieved. Noticeably, decontamination capacity testing of the membrane toward multiple model pollutants demonstrates efficient Pb 2+ adsorption, CR rejection of 89.3 % and superior salt separation. These results confirmed that the incorporation of PANI in PVDF matrix is proposed to provide a promising material for the efficient remove and separate of organic-inorganics in water. Graphical Abstract: ga1 Highlights: High permeability and abundant porosity PANI/PVDF membranes were obtained. Synergistic enhanced effect on Pb 2+ and CR removal was get in co-exist system. Separation of Pb 2+, CR and Na2 SO4 can realized with adsorption and sieving effect.